2014
DOI: 10.1111/imr.12216
|View full text |Cite
|
Sign up to set email alerts
|

A decade of progress in adipose tissue macrophage biology

Abstract: Summary One decade has passed since seminal publications described macrophage infiltration into adipose tissue (AT) as a key contributor to inflammation and obesity-related insulin resistance. Currently, a PubMed search for ‘adipose tissue inflammation’ reveals over 3500 entries since these original reports. We now know that resident macrophages in lean AT are alternatively activated, M2-like, and play a role in AT homeostasis. In contrast, the macrophages in obese AT are dramatically increased in number and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
195
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 186 publications
(206 citation statements)
references
References 146 publications
2
195
0
5
Order By: Relevance
“…Obesity is accompanied by increased infl ammation as evidenced systemically by elevations in circulating infl ammatory cytokines and in adipose tissue due to the accumulation of adipose tissue macrophages (ATMs) ( 6,7 ). ATMs are broadly characterized as classically activated (M1), producing proinfl ammatory proteins, and alternatively activated (M2) macrophages based on their responses to specifi c T helper (Th) 1 and Th2 cytokines (8)(9)(10).…”
mentioning
confidence: 99%
“…Obesity is accompanied by increased infl ammation as evidenced systemically by elevations in circulating infl ammatory cytokines and in adipose tissue due to the accumulation of adipose tissue macrophages (ATMs) ( 6,7 ). ATMs are broadly characterized as classically activated (M1), producing proinfl ammatory proteins, and alternatively activated (M2) macrophages based on their responses to specifi c T helper (Th) 1 and Th2 cytokines (8)(9)(10).…”
mentioning
confidence: 99%
“…8,9,13,14) Hence, given our previous and progressing findings, we considered that cross-talk between adipocytes and macrophages in visceral adipose tissue might play an important role in the development of several diseases. Adipose tissue macrophages are divided into three different phenotypes: classically activated M1 macrophages, alternatively activated M2 macrophages, and deactivated macrophages.…”
Section: )mentioning
confidence: 99%
“…Inflammatory M1 macro- phages produce many pro-inflammatory cytokines which promote inflammation leading to insulin resistance, and promote T helper 1 (Th1) response and possess strong microbicidal and tumoricidal activities, while M2 macrophages are involved in the promotion of T helper 2 (Th2) response, tissue remodeling, immune tolerance, and anti-inflammatory response. 8,15,27,28) Watanabe et al 29) has more recently reported that sepsis induces an incomplete polarization to the M2 macrophages in peritoneal exudate cells in CLP mice. In the present study, CLP markedly enhanced the levels of Arg1 and IL-10 mRNA expression serving as M2 markers in septic mice.…”
Section: -25)mentioning
confidence: 99%
See 1 more Smart Citation
“…At the cellular level, adipocytes produce inflammatory cytokines that enhance the prevalence of local proinflammatory M1 macrophages at the expense of anti-inflammatory and tissue-repairing M2 macrophages 7 . The change in the local cytokine milieu also impacts the local adaptive immune system, by recruiting CD4 + Th1 and CD8 + cytotoxic T cells while depleting Th2 and regulatory T (Tregs) cells involved in tissue homeostasis 8 .…”
Section: Introductionmentioning
confidence: 99%